Experimental evidence of the “Faster is Slower” effect in the evacuation of ants - Soria, Sabrina Andrea (2012)
The faster is slower effect is a self-organized phenomena first described for pedestrian dynamics. Although it has been obtained in computer simulations, it has not been observed in real systems yet. To achieve this goal, we carried out experiments with ants, which are self-propelled biological agents. The ants were placed inside a bidimensional chamber with a narrow exit, and a paper imbibed with repellent was placed in the opposite wall of the chamber. Using different concentrations of citronella, which produced different degrees of repellency, the ants were forced to egress from the chamber and the evacuation time was measured. A minimum evacuation time is observed for intermediate concentrations of citronella, compatible with the faster is slower effect. However, this effect was not generated by the occurrence of blocking clusters right before the exit as the ants did not display a selfish evacuation behavior.